Web-based education of the elderly improves drug utilization literacy: A randomized controlled trial. (January 2021) - Qvarfordt, Maria; Throfast, Victoria; Petersson, Göran; Hammar, Tora; Hellström, Lina
The aim of this study was to explore the effects of web-based education in the field of drug utilization on elderly individuals' knowledge of, concerns about and self-assessed understanding of drug utilization. The 260 included participants were randomized to a control group or an intervention group. To assess drug utilization literacy, we used a questionnaire containing 20 multiple-choice questions on drug utilization and ten statements about drug utilization (to which participants graded their response using a Likert scale: two about common concerns and eight about their self-assessed understanding of drug utilization). The Beliefs about Medicines Questionnaire-General was also used. The intervention group scored higher on the knowledge questions ( p < 0.001) and on six of the eight statements about self-assessed understanding of drug utilization at the first check after 2 weeks ( p < 0.05). At a second check 6 months later, the difference remained for the knowledge questions, but there was no difference in self-assessed understanding of drug utilization between the groups. There were no differences in the concerns about drug utilization or beliefs about medication at any time. We conclude that a web-based education can improve drug utilization literacy in elderly individuals and might contribute to the safer use of medications.